The Impact That Work Environment, Work Motivation, And Work Discipline Have on The Performance of Hammer Strong Bandung Employees - Apriyani, Nenti; Jaya, Rama Chandra; Nuradina, Kartika (Journal of Business and Management Inaba, 2023)
Hammerstout Bandung is a company operating in the field of fashion (clothes), shirts, jeans, sweatshirts, and jackets targeting the young Bandung market. Hammer Stout Bandung produces and sells its brand. This is through sales offline or online with digital marketing. In the 2017-2020 period, Hammerstout Bandung experienced a decline in production which was indicated to be due to various factors that could influence the employee's performance. This research aims to determine and analyze the influence of work discipline, work environment, and work motivation on the performance of Hammer Stout Bandung employees. The total research sample was 63 respondents who were Hammerstout Bandung employees. Data analysis uses multiple linear regression and hypothesis testing. The study's findings demonstrate that work discipline significantly and favorably affects employee performance at Hammerstouth Bandung. Employee performance at Hammerstouth Bandung is positively and significantly impacted by the work environment. Workplace motivation significantly and favorably affects employee performance at Hammerstouth Bandung. With a combined influence contribution of 84.0%, work environment, work motivation, and work discipline have a considerable impact on employee performance in Hammerstouth Bandung. Other characteristics not included in this research account for the remaining 16.0% of the variation in performance.